The effects of context processing on social cognition impairments in adults with Asperger's syndrome - Baez, Sandra; Ibanez, Agustin (Frontiers in Neuroscience, 2014)
Social cognition –the basis of all communicative and otherwise interpersonal relationships– is embedded in specific contextual circumstances which shape intrinsic meanings. This domain is compromised in the autism spectrum disorders, including Asperger’s syndrome (AS) (DSM-V). However, the few available reports of social cognition skills in adults with AS have largely neglected the effects of contextual factors. Moreover, previous studies on this population have also failed to simultaneously (a) assess multiple social cognition domains, (b) examine executive functions, (c) follow strict sample selection criteria, and (d) acknowledge the cognitive heterogeneity typical of the disorder. The study presently reviewed (Baez et al., 2012) addressed all these aspects in order to establish the basis of social cognition deficits in adult AS patients. Specifically, we assessed the performance of AS adults in multiple social cognition tasks with different context-processing requirements. The results suggest that social cognition deficits in AS imply a reduced ability to implicitly encode and integrate contextual cues needed to access social meaning. Nevertheless, the patients’ performance was normal when explicit social information was presented or when the situation could be navigated with abstract rules. Here, we review the results of our study and other relevant data, and discuss their implications for the diagnosis and treatment of AS and other neuropsychiatric conditions (e.g., schizophrenia, bipolar disorder, frontotemporal dementia). Finally, we analyze previous results in the light of a current neurocognitive model of social-context processing.